PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP BOOK-TAX DIFFERENCES PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 – 2020 - Sinaga, Putri Yosepha; Sembiring, Yan Christin (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
From the test results using SPSS, it is known that the coefficient of determination (R Square) of 0.716 means that profitability, leverage and liquidity together affect the difference in book tax, namely 71.6%. Based on the analysis of multiple linear regression equations, it can be said that (1) Profitability has a positive and significant effect on the difference in book taxes in the Basic and Chemical Industry Sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. (2) Leverage has a positive and insignificant effect on the difference book tax on Basic and Chemical Industry Sector companies listed on the Indonesia Stock Exchange for the 2018 - 2020 period. (3) Liquidity has a positive and insignificant effect on the difference in book tax on the Basic and Chemical Industry Sector companies listed on the Indonesia Stock Exchange for the 2018 - 2020 period.   Keywords: Book Tax Difference, Profitability, Leverage, Liquidity